2021
DOI: 10.3390/su13094734
|View full text |Cite
|
Sign up to set email alerts
|

The Green Image in the Spanish Hotel Sector: Analysis of Its Consequences from a Relational Perspective

Abstract: The main objective of this research is to propose a hierarchy of effects model to study three antecedents of green brand image, such as trust, satisfaction and loyalty, and to examine the relationships between these variables. In this context, we investigated how these variables have been applied in the Spanish hotel management strategies for influencing consumer attitude and behavior. To test the proposed model empirically, personal surveys of 732 hotel customers were conducted in five Spanish cities using a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…These actions are also exposed as GM strategies by various studies, where they find that the social responsibility factor plays an important role as a mediator in the effect of the GM on the product or corporate reputation [82] and these, in addition, are related to the consumer's purchasing decision [104]. In this review, it was found that institutional image strategies, the development of the green brand, CSR, green communication, ethical conduct, and the development of organizational culture with green policies have direct effects by increasing trust, word-of-mouth recommendations, credibility, satisfaction, loyalty, perceptions of value, loyalty and purchasing decisions and intentions [4,26,29,31,34,37,43,61,62,65,68,78,79,[86][87][88]. These findings are consistent with the results on the integrity of the brand in the marketing process, implying that one of the attributes most valued by consumers is the personality of the brand developed through specific actions related to the conservation of the environment by companies, which ultimately determines purchasing decisions and raises businesses' reputation [105].…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…These actions are also exposed as GM strategies by various studies, where they find that the social responsibility factor plays an important role as a mediator in the effect of the GM on the product or corporate reputation [82] and these, in addition, are related to the consumer's purchasing decision [104]. In this review, it was found that institutional image strategies, the development of the green brand, CSR, green communication, ethical conduct, and the development of organizational culture with green policies have direct effects by increasing trust, word-of-mouth recommendations, credibility, satisfaction, loyalty, perceptions of value, loyalty and purchasing decisions and intentions [4,26,29,31,34,37,43,61,62,65,68,78,79,[86][87][88]. These findings are consistent with the results on the integrity of the brand in the marketing process, implying that one of the attributes most valued by consumers is the personality of the brand developed through specific actions related to the conservation of the environment by companies, which ultimately determines purchasing decisions and raises businesses' reputation [105].…”
Section: Discussionmentioning
confidence: 95%
“…The second approach is focused on market development and involves carrying out business exchanges with ecological responsibility and with a minimum negative impact on the natural environment [25,27]. The third approach is oriented toward satisfying the needs of two groups of customers: (a) those consumers who have environmentally responsible purchasing behavior; and (b) those consumers who need to develop ecological awareness in their consumption behavior [27][28][29][30][31][32][33][34][35]. A final conceptual approach focuses on green communication, which involves advertising strategies to improve consumer attitudes toward a green brand and influence their purchasing behavior toward green products [26].…”
Section: Green Marketing (Gm)mentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, trust also has an influence on customer loyalty (Alkhurshan & Rjoub, 2020). It is important to every brand to gain trust from the consumer and receive loyalty and decrease risk to change the brand (Fandos-Roig et al, 2020;Sarmiento-Guede et al, 2021). Trust and diversion of struggle have important roles in determining the level of customer loyalty (Alkhurshan & Rjoub, 2020).…”
Section: Trust Customer Satisfaction Customer Loyalty and Happinessmentioning
confidence: 99%